Food neophobia - natural developmental stage or feeding difficulty? A study of children's behavior and parents' knowledge about children’s neophobic behaviors - Białek-Dratwa, Agnieszka; Grajek, Mateusz (Journal of Education, Health and Sport, 2022)
Background: An increasing number of parents report problems with feeding their children to dieticians. Failure to expand the diet or sudden discontinuation of a variety of foods makes them increasingly worried about their child's monotonous diet and mealtime behavior The aim of this study was to assess parents' awareness of food neophobia and the attitudes and behaviors associated with it. Material and method: The study was carried out using a questionnaire-based indirect survey technique using a web form (CAWI). A total of 224 adults (parents of preschool children) participated in the study. The research tool was an anonymous survey questionnaire consisting of three parts. In the last part, a scale concerning neophobic behavior was used. The study group consisted mainly of mothers - 78.3% (n=159); fathers - 21.7% (n= 44). Results: In the study group, no child scored several points indicating a very high probability of neophobia. A high probability is possible in 28 children (13.79%), a possible predisposition to the occurrence of food neophobia exists in 66 children (32.51%), while 109 children (53.69%) do not present a predisposition to food neophobia. Conclusions: The study did not show children's behaviors reported by parents that could indicate a very high probability of food neophobia in their children. Moreover, the results of the questionnaire of neophobia scale indicate that this problem in the studied population concerns about 10% of the examined children.